Perfis, trajetórias e relações de gênero na gestão da educação científica, tecnológica e profissional de Goiás - Pavan, Danielle Fernanda Morais (2017)
The present dissertation has the objective of analyzing the gender relations in management positions in a public institution of scientific, professional and technological education located at the state of Goiás. The management positions differentiate through the content of work, gratifications, diverse levels of power, participation in the deliberative instances, responsibility and institutional visibility. The motivation for the study of the occupation of the management positions of the scientific, professional and technological education is reasoned in the literature that articulates work and gender which reveals the disparities in the access of power charges between men and women, in which women are in the charges of less power and remuneration in the organizations. It was sought to verify if in the educational field, that is characterized for a majority of female presence, if these disparities remained. The methodology used consists in a triangulation of datas and qualitative and quantitative methods. The qualitative approach happened through a semistructured interview. The interviews happened with managers of all levels of the institutional chart and allowed us to understand patterns and differences in the institutional trajectory, verify elements of participation in deliberative instances and observe how men and women articulate work and family. Regarding the quantitative methods, we restored to the elaboration of a questionnaire and data provided by the institution that was researched. The questionnaire tried to obtain data that was not given by the institution such as, for example, race. The data given by the institution made it possible to characterize the profile of people that occupy management positions. The results point to a male predominance in the charges of high management and female predominance in the charges of less power, remuneration and in which participation in the deliberative instances is limited. Besides that, the occupation of the management positions is more favorable to married men then to married women. This can be explained by the fact that the articulation of work and family as well as the institutional trajectories of men and women show themselves distinct, with an overload of work for women.